Hubungan Pendidikan, Pengetahuan dan Paritas dengan Kemampuan Merawat Bayi Baru Lahir - Sitanggang , Sarta Kami; Laia, Sastra Keis; Hardianti, Sartika Putri; Hanum, Parida (Journal of Pharmaceutical and Sciences, 2025)
Background: Neonates are children aged 0 to 28 days. Efforts to establish a healthy lifestyle should begin during the neonatal period, as this is a stage of rapid growth and development. The mother's role is crucial as the primary caregiver, supporting the baby's physical, social, and emotional development. To address various challenges in infants, mothers are required to possess good knowledge and skills in caring for their babies. Objective: To determine the correlation between knowledge, education, and parity on the ability to care for newborns at the Sunggal Primary Clinic. Methods: This study was a quantitative analytical study with a cross-sectional approach. Data were collected through questionnaires and direct interviews with 60 respondents. Data analysis employed univariate and bivariate analysis using the chi-square test, supplemented with the association measure Prevalence Ratio (PR) and 95% Confidence Interval (CI). Results: The bivariate analysis results showed that education (p = 0.000; PR = 3.58; 95% CI: 1.45-8.83), knowledge (p = 0.000), and parity (p = 0.000; PR = 2.79; 95% CI: 1.83-4.24) were significantly associated with the ability to care for newborns. The PR values indicate that mothers with higher education were 3.58 times more likely to be capable of caring for their babies, and mothers with higher parity were 2.79 times more likely. Conclusion: The variables of education, knowledge, and parity have a significant and meaningful relationship with maternal competence in caring for neonates. Education and parity demonstrate a strong influence on the ability to care for newborns.